Measuring the high life: A method for assessing apartment design policy implementation - Paula Hooper; Julian Bolleter; Nicole Edwards; Alexandra Kleeman; Anthony Duckworth; Sarah Foster (MethodsX, 2022)
This paper introduces a comprehensive method to measure the implementation of residential apartment design policies in Australia. It describes a protocol for extracting and measuring potentially health-enhancing policy-specific design requirements derived from three current residential apartment design policies in Sydney, Melbourne and Perth. These requirements focus on ten key design elements: (1) solar access, (2) natural ventilation, (3) private open space, (4) communal open space, (5) circulation spaces, (6) acoustic privacy, (7) outlook and (8) visual privacy, (9) bicycle and car parking and (10) apartment mix. This paper also describes the computation of scores to quantify the levels of on-ground implementation of the design requirements and compliance with the policies. The method will allow researchers to objectively quantify, benchmark and assess the uptake of apartment policy in apartment design and construction to inform future policy development.• Measurements were developed to systematically assess apartment buildings for their implementation of specific design requirements stipulated by State Government design policies.• Policy implementation was defined as the degree to which the apartment buildings adhered to the requirements outlined by the apartment design policies. A scoring system was developed to quantify policy implementation at both the apartment and building levels.• This method can be replicated to allow researchers to objectively quantify, benchmark and assess the uptake of apartment policy in apartment design and construction to inform future policy development.